PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN LUBUK BAJA BATAM - Zianatika, Dwi; S.E.,M.M, Dr.Wasiman (LPPM Universitas Putera Batam, 2022)
Human resources are the most significant asset in achieving the goals of an organization,because they have an important role in every organizational activity. Without the role of humans, activities in organizations cannot run properly. In this case, it shows that human resources are the main key that should be thought of. To determine the effect of leadership style, employee performance, on employee performance and the effect of leadership style and work discipline together on employee performance at the Lubuk Baja District Office, Batam City. The research method uses associative quantitative research, with data analysis techniques validity test, reliability test, normality test, multicollinearity test, descriptiveanalysis, multiple linear regression analysis, coefficient of determination (r2), t test (alone), f test together). The outcomes showed that there was an influence of leadership style, work discipline on the performance of the employees of the Lubuk Baja District Office. The conclusion shows that the influence of leadership style on employee performance is 18.9%. And the effect of work discipline on employee performance is 55.5%. And the influence of leadership style and work discipline on performance is 25.6% Keywords: Leadership Style, Work Discipline, Employee Performance